The VapBC-4 Characterization Indicates It Is a Bona Fide Toxin-Antitoxin Module of Leptospira interrogans: Initial Evidence for a Role in Bacterial Adaptation - Bruna Oliveira Pigatto Azevedo; Deborah Kohn Damiano; Aline Florencio Teixeira; Ana Lucia Tabet Oller Nascimento; Luis Guilherme Virgilio Fernandes; Alexandre Paulo Yague Lopes (Microorganisms)
Toxin-antitoxin (TA) systems are one of the bacterial adaptation mechanisms to adverse conditions. Leptospira interrogans serovar Copenhageni contains nine putative TA systems. To date, only VapBC-3 and VapBC-1 have been experimentally characterized and considered functional modules. This study shows that the VapBC-4 module is a novel bona fide TA system constituted by VapB-4 antitoxin and VapC-4 toxin. Overexpression of the recombinant toxin in Escherichia coli resulted in growth inhibition, which was rescued by co-expression of the VapB-4 antitoxin. The toxin-antitoxin binding capability, essential to TA functionality, was demonstrated by dot blot assay in vitro, while the pull-down assay indicates that the toxin and antitoxin interact in vivo. In addition, we confirmed that VapC-4 is a PIN domain endoribonuclease capable of degrading viral MS2 substrate. The transcriptional studies suggest that vapC-4 may be involved in the virulence and adaptability of L. interrogans serovar Copenhageni for adverse environmental conditions. Taken together, these results show that the VapBC-4 module is functional and can be considered a bona fide module.